Comparison of serum electrolytes in children with febrile seizures to febrile children without seizures: a case control study - Jayasurya, K.; Singhal, Pankaj Kumar; Gaba, Manav; Mathur, Gaurav (International Journal of Contemporary Pediatrics, 2024)
Background: Febrile seizures (FS) are the most common type of seizures in children aged 6 to 60 months, occurring during fever episodes without underlying CNS infections or prior afebrile seizures. Electrolyte imbalances are thought to contribute to FS, but their exact role remains unclear. This study aimed to investigate the association between serum electrolyte levels (sodium, potassium, calcium and magnesium) in children with febrile seizures and compare them to febrile children without seizures. Methods: A case-control study was conducted at the JK Lon Children and Mothers Hospital, Government Medical College, Kota, Rajasthan, over four months. Sixty-one children with febrile seizures were identified as cases and 60 febrile children without seizures served as controls. Data on sociodemographic and clinical parameters, including serum electrolyte levels, were collected. Chi-square tests and t-tests were used to analyse categorical and continuous variables, respectively. Results: Significant differences were found in serum calcium and potassium levels between the two groups. Hypocalcemia was more prevalent in controls (75%) compared to cases (29.51%) (p=0.000), while hypokalemia was also higher in controls (35%) than in cases (6.56%) (p=0.000). No significant differences were observed in sodium and magnesium levels between the groups. Conclusions: Calcium and potassium levels appear to be associated with the occurrence of febrile seizures in children, while sodium and magnesium levels showed no significant differences. Further studies are needed to clarify the role of electrolytes in FS pathogenesis.